Physiological and metabolic shifts associated with yield-related parameters in pepper (Capsicum chinense) swayed by nitrogen supply - Silva, Lucas de Ávila (2019)
Among the essential elements for plants, nitrogen (N) is highlighted due to the large amounts uptake and the close relationship between carbon (C) and N metabolism. Despite its importance, little is known about the role of the N supply on physiological and metabolic traits as well as its relation with the yield-related parameters in Capsicum. For this, in this work, the natural variation of fruit set, fruit size, and leaf morphology between two commercial cultivars of C. chinense, Biquinho and Habanero, was explored. First, plants of both cultivars were submitted to increasing doses of N. In this study (Chapter 1), both cultivars increased the biomass allocation to leaves in conditions of higher N supply. Plants growing under N-deficiency produced a lower number of flowers and heavier fruits. Contrarily, plants under high N condition tended to decrease their CO2 assimilation rates, harvest index and fruit weight. The continuous formation of new reproductive sinks was as an important factor to tolerate the N excess. The results suggest that N supply acts on the sucrose supply to different organs and can influence yield-related traits between Capsicum cultivars. Subsequently, the same cultivars were submitted to moderate N deficiency or N sufficiency combined with unshaded or shaded conditions to better understand the role of source strength on fruit set at the metabolic level (Chapter 2). The metabolic balance of different metabolites at source leaves and flowers during the flowering period was assessed. Higher fruit set was mainly related to the export of both sucrose and amino acids from source leaves to flowers. Additionally, starch turnover in source leaves but not in flowers played a central role on the sucrose supply to sink organs at night. As biometric parameters used to evaluate the relationship between the leaf area and mass such as the specific leaf area (SLA) are often related to growth, the behavior of SLA in relation to the N supply was assessed in the Chapter 3. Overall, we observed that both genotypes showed a decrease in SLA according to the increase of N supply. Our results suggest the common SLA behavior occur due to the role of N metabolism-related metabolites variation, in special amino acids, protein, and starch, influencing the leaf density. However, in the range of moderate N deficiency to N sufficiency, the genotypes showed a distinct response of SLA in relation to the N supply due to the genotypic alterations on palisade and spongy parenchyma. Taken as a whole, the results indicated important metabolic and physiological traits associated with growth- or yield-related parameters of Capsicum plants. However, further studies are necessary to identify genes related to the traits highlighted in the studies presented, using mapping techniques together with populations of landrace accessions, as reviewed in Chapter 4. Following the identification of the genes, important traits can be tested and used in breeding programs of Capsicum and other plant species.